Incidence of death or disability at 6 months after extracorporeal membrane oxygenation in Australia: a prospective, multicentre, registry-embedded cohort study. Issue 11 (November 2022) - Hodgson, Carol L; Higgins, Alisa M; Bailey, Michael J; Anderson, Shannah; Bernard, Stephen; Fulcher, Bentley J; Koe, Denise; Linke, Natalie J; Board, Jasmin V; Brodie, Daniel; Buhr, Heidi; Burrell, Aidan J C; et al.
Summary: Background: Extracorporeal membrane oxygenation (ECMO) is an invasive procedure used to support critically ill patients with the most severe forms of cardiac or respiratory failure in the short term, but long-term effects on incidence of death and disability are unknown. We aimed to assess incidence of death or disability associated with ECMO up to 6 months (180 days) after treatment. Methods: This prospective, multicentre, registry-embedded cohort study was done at 23 hospitals in Australia from Feb 15, 2019, to Dec 31, 2020. The EXCEL registry included all adults (≥18 years) in Australia who were admitted to an intensive care unit (ICU) in a participating centre at the time of the study and who underwent ECMO. All patients who received ECMO support for respiratory failure, cardiac failure, or cardiac arrest during their ICU stay were eligible for this study. The primary outcome was death or moderate-to-severe disability (defined using the WHO Disability Assessment Schedule 2.0, 12-item survey) at 6 months after ECMO initiation. We used Fisher's exact test to compare categorical variables. This study is registered with ClinicalTrials.gov, NCT03793257 . Findings: Outcome data were available for 391 (88%) of 442 enrolled patients. The primary outcome of death or moderate-to-severe disability at 6 months was reported in 260 (66%) of 391 patients: 136 (67%) of 202 who received veno-arterial (VA)-ECMO, 60 (54%) of 111 who received veno-venous (VV)-ECMO, and 64 (82%) of 78 who received extracorporeal cardiopulmonary resuscitation (eCPR). After adjustment for age, comorbidities, Acute Physiology and Chronic Health Evaluation (APACHE) IV score, days between ICU admission and ECMO start, and use of vasopressors before ECMO, death or moderate-to-severe disability was higher in patients who received eCPR than in those who received VV-ECMO (VV-ECMO vs eCPR: risk difference [RD] –32% [95% CI –49 to –15]; p<0·001) but not VA-ECMO (VA-ECMO vs eCPR –8% [–22 to 6]; p=0·27). Interpretation: In our study, only a third of patients were alive without moderate-to-severe disability at 6 months after initiation of ECMO. The finding that disability was common across all areas of functioning points to the need for long-term, multidisciplinary care and support for surviving patients who have had ECMO. Further studies are needed to understand the 180-day and longer-term prognosis of patients with different diagnoses receiving different modes of ECMO, which could have important implications for the selection of patients for ECMO and management strategies in the ICU. Funding: The National Health and Medical Research Council of Australia.